Assertive Behavior of Minangkabau and Batak Implications In Development Services Social Capability - Nurul Fajri; Herman Nirwana; Alizamar Alizamar (Global Econedu, 2019)
One of the roles of BK Counselors in schools is to assist students to become independent and optimally developed in various fields such as social interaction. It is greatly influenced by assertive behavior. The research determines the assertive behavior in men and women using Minangkabau and Batak cultures as a case study. The sample used in this study was 413 which comprises of191 Minangkabau students and 222 Batak students selected by the cluster random sampling technique. Therefore, the instrument used in this study is the scale of assertive behavior with a reliability level of 0.930. The findings of the research show a medium attribute with significant differences in both cultures. Therefore, it is recommended that counselors make use of structuring techniques, while explaining the principle of confidentiality and openness to students.